Jacks of All Trades: The Lived Experiences of Out-of-Field Non-Government Basic Education Teachers - Calaguas, Glenn; Dungca, Elmer (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: Out-of-field teaching is a concern that results in teaching ineffectiveness, compromising quality education. However, there is still limited extant literature available, particularly on the experiences of non-government junior high school teachers. This study specifically explored the lived experiences of the out-of-field teachers in the provinces of Pampanga and Tarlac in the Philippines. Methodology: Ten basic education teachers particularly junior high school teachers were tapped in order to achieve the purpose of the study. Also, maximum variation was utilized, incorporating convenience and snowball techniques to ensure diverse perspectives. The Colaizzi method in analyzing the data was used through a positivist view. Member checking was equally observed to meticulously capture the core experiences of the informants and to ensure the trustworthiness of the data.] Main Findings: The findings unveiled both positive and negative experiences that were eventually clustered into five categories: (1) challenges of out-of-field teaching, (2) strategies to overcome challenges, (3) opportunities for growth, (4) impact on students, and (5) areas for improvement. Consistent with the recent works of literature, this study highlights the contrasting aspects of out-of-field teaching—its challenges and potential opportunities. Novelty/Originality of this study: As a contrast to the usual assumption that out-of-field teaching only creates negative experiences, not only among teachers but also among learners, the challenges and opportunities of this phenomenon offer valuable insights that can serve as a cornerstone for policymakers and school administrators in helping and supporting out-of-field teachers. Contextualized assistance and targeted preparations can guarantee quality education